A reassessment of Mappia (Icacinaceae) taxonomy using environmental data - Duno de Stefano, Rodrigo; Loera, Israel; Angulo, Diego Francisco (Instituto de Ecología, A.C., 2020)
Background and Aims: Mappia (Icacinaceae) is a genus comprising four species inhabiting Mesoamerica and the Greater Antilles. In the most recent phylogenetic analysis based on morphological data, three species, representing a continental clade (Mappia longipes, M. mexicana and M. multiflora) sister to the Antillean species M. racemosa, were supported. Our aims in this study were to evaluate whether environmental data support the previous hypothesis in Mappia entities. Methods: In this study, we use ecological niche analysis (environmental niche modeling and niche divergence/conservatism tests) and multivariate analysis of variance (MANOVA) to test the previous morphological hypothesis at species and infraspecific level. Key results: Ecological differentiation between M. multiflora distributed from southeast Mexico to Costa Rica and M. racemosa occurring in Cuba, Jamaica, and Puerto Rico (Greater Antilles) was found, but not between the infraspecific taxa within the Antilles (M. racemosa var. brachycarpa, and M. racemosa var. racemosa). Conclusions: Our study brings an important signal of the ecological divergence between closely related species, but with disjunct patterns of distribution.